Regulatory mechanisms of autophagy-related ncRNAs in bone metabolic diseases - Yan, Binghan; Li, Zhichao; Su, Hui; Xue, Haipeng; Qiu, Daodi; Xu, Zhanwang; Tan, Guoqing (Frontiers in Pharmacology, 2023)
Bone metabolic diseases have been tormented and are plaguing people worldwide due to the lack of effective and thorough medical interventions and the poor understanding of their pathogenesis. Non-coding RNAs (ncRNAs) are heterogeneous transcripts that can’t encode the proteins but can affect the expressions of other genes. Autophagy is a fundamental mechanism for keeping cell viability, recycling cellular contents through the lysosomal pathway, and maintaining the homeostasis of the intracellular environment. There is growing evidence that ncRNAs, autophagy, and crosstalk between ncRNAs and autophagy play complex roles in progression of metabolic bone disease. This review investigated the complex mechanisms by which ncRNAs, mainly micro RNAs (miRNAs), long noncoding RNAs (lncRNAs), and circular RNAs (circRNAs), regulate autophagic pathway to assist in treating  bone metabolism disorders. It aimed at identifying the autophagy role in bone metabolism disorders and understanding the role, potential, and challenges of crosstalk between ncRNAs and autophagy for bone metabolism disorders treatment.